2014
DOI: 10.1007/s11064-014-1270-x
|View full text |Cite
|
Sign up to set email alerts
|

Impairments in Brain-Derived Neurotrophic Factor-Induced Glutamate Release in Cultured Cortical Neurons Derived from Rats with Intrauterine Growth Retardation: Possible Involvement of Suppression of TrkB/Phospholipase C-γ Activation

Abstract: Low birth weight due to intrauterine growth retardation (IUGR) is suggested to be a risk factor for various psychiatric disorders such as schizophrenia. It has been reported that developmental cortical dysfunction and neurocognitive deficits are observed in individuals with IUGR, however, the underlying molecular mechanisms have yet to be elucidated. Brain-derived neurotrophic factor (BDNF) and its receptor TrkB are associated with schizophrenia and play a role in cortical development. We previously demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
0
4
0
1
Order By: Relevance
“…Study had shown that reduced of BDNF mRNA could lead to similarly a low level of NAA, and it is closely related to age-dependent cognitive behavioral decline [ 33 ]. In addition, BDNF induced Glu release through activation of the TrkB/phospholipase C-γ (PLC-γ) pathway [ 34 36 ]. It indicates that the PLC-γ pathway which activated by the BDNF-TrkB signal is necessary to stimulate Glu release.…”
Section: Discussionmentioning
confidence: 99%
“…Study had shown that reduced of BDNF mRNA could lead to similarly a low level of NAA, and it is closely related to age-dependent cognitive behavioral decline [ 33 ]. In addition, BDNF induced Glu release through activation of the TrkB/phospholipase C-γ (PLC-γ) pathway [ 34 36 ]. It indicates that the PLC-γ pathway which activated by the BDNF-TrkB signal is necessary to stimulate Glu release.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence also demonstrates that BDNF exhibits a protective role against AD pathogenesis ( Colucci-D'Amato et al, 2020 ; de Pins et al, 2019 ; Liao et al, 2021 ). BDNF has also been shown to enhance the release of neurotransmitters, including glutamate, via various different pathways ( Jovanovic et al, 2000 ; Leal et al, 2014 ; Numakawa et al, 2014 ). In our previous study, we found that the levels of BDNF were decreased in the hippocampus of AD rats but increased following treatment with BSTSF ( Sheng et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The most important gene in this aspect is the brain-derived neurotrophic factor (BPDNF), which has been studied in suicide, as well as in schizophrenia. Interestingly, BPDNF and its receptor TrkB induce glutamate release through activation of a pathway involving PLC isoforms in developing cultured cortical neurons [101].…”
Section: Plc Signaling In Suicidementioning
confidence: 99%